STRATEGI PEMASARAN SEKOLAH MENENGAH ATAS SWASTA BERASRAMA DI KABUPATEN SEMARANG 1 - Tyagita, Brigitta Putri Atika (Kelola: Jurnal Manajemen Pendidikan, 2016)
This study aimed to describe the success of marketing strategies in SMA Sedes Sapientiae Jambu which is a high boarding school in Bedono, Semarang regency with its students coming from various cities in Indonesia, such as Palembang, Lampung, Jakarta, Bogor, Semarang , Yogyakarta, Bali, Makassar and Papua. The diversity of high school students Sedes Sapientiae Jambu is becausethe success of marketing management at SMA Sedes Sapientiae Jambu Bedono, where in the executing the marketing strategy there is a special team and they did not hesitate to invite an expert in the field of marketing to teach the promotion team to do marketing. In addition, many of the activities carried out in marketing schools such as by visiting junior high schools in various regionsof Java and Jakarta region and made a presentation as Sedes Sapientiae Jambu students as keynote speaker, did a choir at churches, did a tty out for the junior and open house in SMA Sedes Sapientiae Jambu, besides that, establishing relationships with alumni who are in various cities in Indonesia. Data collection techniques in this research through interviews, participatory observationand documentation, and data analysis performed continuously throughout the study. One of the keys of the succesful of marketing in SMA Sedes Sapientiae Jambu the activities that establish a good relationship with various secondary schools in various regions, relations with alumni, parents, committee and local residents. The evidenced of it by the increasing number of high school students in Sedes Sapientiae Jambu from year to year. In this paper the writer recommend ways of marketing carried out by SMA Sedes Sapientiae Jambu that can be applied in other schools to increase student numbers.